Detection of Fault and Fracture Using Seismic Diffraction and Behaviour of Diffraction Hyperbola with Velocity and Time - Yasir Bashir, Deva Ghosh, Chow Weng Sum, . (2015)
Seismic diffractions are often considered as noise and during processing it has been suppress intentionally or implicitly. Diffraction hyperbola actually have information of true diffraction, wave propagation and/or fracture waves which always contain valuable information of subsurface and helps in better imaging and reservoir characterization. Using double radical equation and synthetic data we examine the diffraction hyperbola behaviour using different velocity and depth